Evaluation of Metarhizium anisopliae var. anisopliae (Deuteromycotina: Hyphomycete) isolates and their effects on subterranean termite Coptotermes curvignathus (Isoptera: Rhinotermitidae) - Hoe, Pik Kheng; Bong, Joseph Choon Fah; Kadir, Jugah; Amarthalingam, Rajan (Science Publications, 2009)
Problem statement: Coptotermes curvignathus (Isoptera: Rhinotermitidae) is a common termite pest found in oil palm plantation planted on peat. Currently, the control methods focus on using insecticides that lead to high cost and adverse effect to the environment. Approach: Biological control like the use of entomopathogens provides an alternative control method for termite infestation problem. However, several factors need to be investigated in order to obtain a virulent strain with potential to be developed into a biopesticide. Results: Three local isolates (MG, LR2 and TA) of Metarhizium anisopliae were obtained and identified as M. anisopliae var. anisopliae using molecular techniques. Growth performance of isolates on four basal media namely, Potato Dextrose Agar (PDA), Potato Dextrose Agar with 1% yeast extract (PDAY), Sabaroud Dextrose Agar (SDA) and Sabaroud Dextrose Agar with 1% yeast extract (SDAY) was assessed. The pathogenicity of each isolate was tested against subterranean termite Coptotermes curvignathus at three concentrations of 1×106, 1×107 and 1×108 conidia mL-1. Infections of the isolates were examined using electron microscopy technique. The growth performance of each isolate differed significantly. Among all basal media, only SDAY was able to produce high growth performance and thick conidia mats with all isolates. The most pathogenic isolate was LR2, which caused 100% mortality at 1×107 conidia mL-1 within 3 days post-inoculation. Conclusion/Recommendations: All three isolates were pathogenic against C. curvignathus as they were able to germinate and penetrate into the termite cuticle within 15 hours post-inoculation. The three local isolates of M. anisopliae var. anisopliae have potential to be developed as biopesticides to control termites, C. curvignathus in oil palm plantations.